Manfaaat Museum Simalungun Dalam Meningkatkan Pengetahuan Sejarah dan Seni Budaya - Khottob Idris; Toga Hotdianto Damanik; Jantri Hotdi Sinaga; Sonia A. Butar-Butar; Eirin Kristin Girsang; Siti Salsabila Putri Ajf; Dian G. Purba Tambak (Student Scientific Creativity Journal, 2024)
Museums play a central role in maintaining, preserving, and teaching cultural heritage to the public. This article discusses the important role of museums as cultural institutions that have the responsibility of preserving and presenting cultural heritage for future generations. Museums are not only repositories of historical artifacts, art, and knowledge, but also educational centers that provide in-depth insights into history, art, and culture.This article discusses two main aspects of the museum's role: preservation and education. First, museums function as custodians of cultural heritage by collecting, caring for and preserving historical artifacts and objects. Thus, museums become a bulwark against the loss of cultural and historical identity. Second, museums as educational institutions provide opportunities for the public to gain in-depth knowledge about various aspects of human life through exhibitions, educational programs, and interactive activities.